Modeling of technical management information system with UML and implementation using the combination of PHP and MYSQL - Nik Mahamood, Nik Maria (Universiti Teknologi Malaysia, 2003)
This paper focuses on modeling of system using Unified Modeling Language notations and its implementation using Hypertext preprocessor (PHP) and MySQL. The Unified Modeling Language is one of the modeling languages for object-oriented analysis and design, which provide a set of concepts, and notations that can be used throughout the entire software development process. PHP is a scripting language, which embedded in Hyper Text Mark Language and interpreted by the server. It used to manage dynamic content databases, work with databases, handle session tracking and even build entire e-commerce sites. MySQL is the popular database management system, which offers a rich and very useful set of functions. This paper describes the process of modeling system with UML, and why the combination of Hypertext Preprocessor and MySQL selected for developing the system